Pathological Significance and Prognostic Roles of Indirect Bilirubin/Albumin Ratio in Hepatic Encephalopathy - Li, Yanling; Liu, Huiyuan; Chen, Keng; Wu, Xueheng; Wu, Jiawen; Yang, Zhenjun; Yao, Leyi; Wen, Guanmei; Zhang, Change; Chen, Xin; Chen, Xiaohui; Tang, Daolin; et al. (Frontiers in Medicine, 2021)
Background and Aim: Hepatic encephalopathy (HE) is a neurological disease caused by severe liver disease. Early identification of the risk factor is beneficial to the prevention and treatment of HE. Free bilirubin has always been considered to be the culprit of neonatal kernicterus, but there is no research to explore its role in HE. In this study, we aim to study the clinical significance of the indirect bilirubin-albumin ratio in HE. Methods: A retrospective case-control study of 204 patients with liver failure was conducted. Human serum albumin (HSA) or heme oxygenase-1 (HO-1) inhibitor SnPP (Tin protoporphyrin IX dichloride) was injected intraperitoneally into Ugt1−/− mice to establish a treatment model for endogenous hyperbilirubinemia. Results: IBil/albumin ratio (OR = 1.626, 95% CI1.323–2.000, P < 0.001), white blood cell (WBC) (OR = 1.128, 95% CI 1.009–1.262, P = 0.035), ammonia (OR = 1.010, 95% CI 1.001–1.019, P = 0.027), platelet (OR=1.008, 95% CI 1.001–1.016, P = 0.022), Hb (OR = 0.977, 95% CI 0.961–0.994, P = 0.007), and PTA (OR = 0.960, 95% CI 0.933–0.987, P = 0.005) were independent factors of HE. Patients with a history of liver cirrhosis and severe HE (OR = 12.323, 95% CI 3.278–47.076, P < 0.001) were more likely to die during hospitalization. HSA or SnPP treatment improved cerebellum development and reduced apoptosis of cerebellum cells. Conclusion: The IBil/albumin ratio constitutes the most powerful risk factor in the occurrence of HE, and reducing free bilirubin may be a new strategy for HE treatment.